Classroom Management through The Bel Canto and Chinese Popular Song - Zheyan, Zhang; Banchongsilpa, Orawan; Klaywong, Sinam (International Journal of Multidisciplinary in Management and Tourism, 2025)
This article aims to study Classroom Management through The Bel Canto and Chinese Popular Song. The research sample consists of three instructors and ninety students. The research instruments include interviews and classroom observations. Researcher observed the vocal classes at Guizhou University for a period of 16 weeks. The findings revealed three management aspect in teaching 1. The integration of musical knowledge. The instructor designed the teaching content to study the musical styles. Legend, The Great Sky, Longing, and study in popular style song: Love is Forever, Waiting. Additionally, there were songs assigned for students to integrate both musical styles, which include: Slowly Liking You, Heavenly Road, On the Water Side. the evaluation focus on musical skills: Focus, Technique, Position, Expression. And Adaptation to Chinese Language and Culture. The classroom environment was managed by selecting music rooms with spacious areas that closely resemble performance stages. 3. Promoting Discipline. The instructor promoted discipline through In-Class Practice and Out-of-Class Practice, with detailed monitoring of practice progress. The results of this study indicate that the classroom management in three aspects at Guizhou University is well-prepared in terms of facilities, content integration, and discipline promotion. These elements are structured to enhance classroom efficiency and promote effective learning.